Acute Heat Stress Alters the Expression of Orexin System in Quail Muscle - Nguyen, Phuong H.; Greene, Elisabeth; Kong, Byung-Whi; Bottje, Walter; Anthony, Nicholas; Dridi, Sami (Frontiers in Physiology, 2017)
Accumulating evidences indicate that the hypothalamic neuropeptide orexins or hypocretins are involved in stress-induced responses in mammals. Recently, we found that orexin is expressed and secreted from avian muscle cells, however its regulation is still unknown. In this study, we investigated the effect of heat and oxidative stress, the most challenging stressors in poultry production, on the expression of orexin system in quail muscle tissues and myoblast cell lines. Four week-old genetically selected susceptible and resistant Japanese quail (Coturnix coturnix Japonica) lines were exposed to acute heat stress (HS, 37oC for 1.5h) or maintained at thermoneutral conditions (22oC). Quail myoblast (QM7) cell line was exposed to heat stress (45oC) for 0.5, 1, 2 or 4 h. The control cells were maintained at 37oC. The cells were also treated with several doses of hydrogen peroxide (H2O2, 10-200 µM) or 4-Hydroxynonenal (4-HNE, 10-30 µM) as oxidative stress. Untreated cells were used as controls. Acute HS significantly induced the expression of HSP70 and down-regulated orexin system in both quail muscle tissue and QM7 cells. Similarly, H2O2 but not 4-HNE treatment significantly increased HSP70 protein levels and dysregulated the expression of orexin and its related receptors in a dose-dependent manner in QM7 cells. Transient overexpression of HSP70 down-regulated the expression of orexin system in QM7 cells. Taken together, these data indicate that orexin may be a key player in stress response in avian muscle by demonstrating that heat and oxidative stress alter the expression of orexin system in quail muscle. This effect might be mediated through HSP70. Unraveling the upstream regulators and downstream effectors of orexin in avian muscle merits further in depth investigations.